Fallas longitudinales y transversales en la sabana de Bogotá, Colombia (2002)
A structural model for the Sabana de Bogotá area was obtained from interpreting Landsat images, vertical electrical soundings, well litological logs and existing geological maps. NE longitudinal faults are related to thrust and backthrust, they may also be reversed faults with lateral displacements as a result of transpressional tectonics. For some of them, some continuity under the unconsolidated cover is infered. NW transverse faults can be interpreted as lateral thrust ramps or sinestral strike slip structures. This fault interaction shaped a paleo-topography where blocks, including Cretaceous and Paleogene units, were indistinctly covered by Neogene-Quaternary deposits. This proposal allows some understanding on the hydrogeological system for the Sabana de Bogotá area, disproving the idea of lateral continuity of Paleogene units. Some of these faults suggest neotectonic activity.